(untitled) (TRISANGAM INTERNATIONAL REFEREED JOURNAL, 2025)
Psychoanalysis and psychology have significantly influenced the world of thought and medical science. In 1896, Austrian neurologist Sigmund Freud first introduced the concept of ‘Psychoanalysis’. This therapeutic method of Sigmund Freud has become one of the most important treatment methods in the modern world. Humayun Ahmed, one of the most popular fiction writers in Bangladesh and Bengali literature, has consciously highlighted the aspect of psychoanalysis in his various novels. Humayun Ahmed’s best novel series is ‘Misir Ali’. The protagonist of this novel series, Misir Ali, is a psychology professor and psychoanalyst. Although he does not practice psychotherapy as a profession, he does it out of his own liking. And so, people come to Misir Ali with various problems. The first novel in the ‘Misir Ali’ series is ‘Devi’. In this novel, Humayun Ahmed has very consciously shaped the subject of psychoanalysis. The method of psychoanalysis of psychologist Sigmund Freud was primarily conversational. He would talk to the patient and point out the cause of the disease. He observed that in many cases, the disease was cured by bringing the cause to the forefront. Again, in many cases, he would hypnotize the patient and remove the symptoms of the disease from the patient’s mind. In the novel ‘Devi’, Misir Ali seems to have followed the path indicated by Sigmund Freud in Ranu’s treatment method. Humayun Ahmed’s second novel in the ‘Misir Ali’ series is ‘Nishithini’. The subject of psychoanalysis has also come up in this novel. The subject of psychoanalysis has also come up in Humayun Ahmed’s novel ‘Misir Ali. Kothay?’ In the novel, it is seen that when Tariqul Islam suddenly becomes overwhelmed by a fear of dogs, Misir Ali treats him using the hypnotic method. Humayun Ahmed has presented Misir Ali as an experienced psychoanalyst. However, the steps of treatment that the novelist has described here are completely fictional and dramatic.